Phenyl glycidyl ether as an effective noncovalent functionalization agent for multiwalled carbon nanotube reinforced polyamide 6 nanocomposite fibers. (16th June 2019) - Park, Min; Lee, Hyeseong; Jang, Ji-un; Park, Jong Hyuk; Kim, Chai Hwan; Kim, Seong Yun; Kim, Jaewoo
Abstract: Techniques for optimizing the dispersion of carbon nanotubes in composites by applying small amounts of additives in a simple manner are recognized as one of the most important core technologies in nanocomposite engineering. In this study, we reported the feasibility of phenyl glycidyl ether (PGE) as an effective noncovalent functionalization agent and suggested a facile and low-temperature process that applied high-speed rotation based on a planetary centrifugal mixer to improve the dispersion of multiwalled carbon nanotube (MWCNT) in the polyamide 6 (PA6) composite. PGE molecules were introduced on MWCNTs based on the π-π* interaction, resulting in enhanced MWCNT dispersion by preventing of the aggregation between the MWCNTs due to the van der Waals force. The tensile strength of the PA6 composite fiber filled with 1 wt% MWCNTs was improved up to 31.8% by the PGE treatment, indicating that PGE molecules were an effective noncovalent functionalization agent.